Technology advancements in enhancing cash waqf contribution: a survey on public acceptance of technology / Wan Musyirah Wan Ismail, Mohamed Saladin Abdul Rasool and Abd Halim Mohd Noor - Wan Ismail, Wan Musyirah; Abdul Rasool, Mohamed Saladin; Mohd Noor, Abd Halim (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Cash waqf plays a significant role in the economy and society in the country and plays a vital role in advancing the socio-economic well-being of the Muslim community. Scholars believe that waqf contribution by using cash is much important and more relevant due to its flexibility than waqf properties in the present day. In Malaysia, cash waqf is one of the alternative instruments that can improve social welfare and reduce the poverty rate and, at the same time, lessen the burden of the government. Many ways have been proposed to encourage society to contribute cash waqf for the benefits of the ummah. Therefore, this paper aims to identify the behavior that influences the contribution of cash waqf in Malaysia using the Theory of Planned Behavior (TPB). In line with technology advancement, it is expected that technology adoption in the method of collecting cash waqf could be a stepping stone to increase the amount of funds. With this reason, technology acceptance and technology usage will be proposed to enhance the contribution of cash waqf. This study used 138 respondents who were employed Muslims to identify the factor influence contribution of cash waqf. The statistical Package for Social Science (SPSS) was used to analyse data through descriptive and correlation analysis. Based on the descriptive analysis, the results revealed that most of the respondents were female, working in the private sector and aged between 35 to 40 years old. Referring to the correlation analysis, the finding discovered a positive and strong relationship between technology acceptance and contribution of cash waqf, so it can be summarized that technology acceptance could influence people to contribute cash waqf as technology advancement is implemented in the method of collection.